Integrin binding by Borrelia burgdorferi P66 facilitates dissemination but is not required for infectivity. (16th February 2015) - Ristow, Laura C.; Bonde, Mari; Lin, Yi‐Pin; Sato, Hiromi; Curtis, Michael; Wesley, Erin; Hahn, Beth L.; Fang, Juan; Wilcox, David A.; Leong, John M.; Bergström, Sven; Coburn, Jenifer
Summary P66, a Borrelia burgdorferi surface protein with porin and integrin‐binding activities, is essential for murine infection. The role of P66 integrin‐binding activity in B. burgdorferi infection was investigated and found to affect transendothelial migration. The role of integrin binding, specifically, was tested by mutation of two amino acids (D205A, D207A) or deletion of seven amino acids (Del202–208). Neither change affected surface localization or channel‐forming activity of P66, but both significantly reduced binding to αvβ3. Integrin‐binding deficient B. burgdorferi strains caused disseminated infection in mice at 4 weeks post‐subcutaneous inoculation, but bacterial burdens were significantly reduced in some tissues. Following intravenous inoculation, the Del202–208 bacteria were below the limit of detection in all tissues assessed at 2 weeks post‐inoculation, but bacterial burdens recovered to wild‐type levels at 4 weeks post‐inoculation. The delay in tissue colonization correlated with reduced migration of the Del202–208 strains across microvascular endothelial cells, similar to Δp66 bacteria. These results indicate that integrin binding by P66 is important to efficient dissemination of B. burgdorferi, which is critical to its ability to cause disease manifestations in incidental hosts and to its maintenance in the enzootic cycle.